Neurofibroma of the maxillary antrum: A rare case - Jain, Deepali (Medknow Publications & Media Pvt Ltd, 2014)
Neurofibromas are benign tumors of peripheral nerve tissue, frequently associated with neurofibromatosis type 1. Their isolated occurrence in the maxillary antrum is rare, with only 6 cases described in the English literature to the best of our knowledge. Primary neurogenic tumors in the maxillary sinus are unusual entities. The majority of the reported cases that have dealt with neurilemmomas and isolated neurofibromas are extremely rare. Here, a case of neurofibroma of the maxillary sinus. We present the case of a 60-year-old female patient with the chief complain of growth in the upper right back region of the jaw, which was preceded by exfoliation of teeth in the same region 1 month back.